Transplantation of Donor‐Origin Mouse Embryonic Stem Cell‐Derived Thymic Epithelial Progenitors Prevents the Development of Chronic Graft‐versus‐Host Disease in Mice. (2nd August 2016) - Hu, Rong; Liu, Yalan; Su, Min; Song, Yinhong; Rood, Debra; Lai, Laijun
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy for many malignant and nonmalignant diseases. However, chronic graft‐versus‐host disease (cGVHD) remains a significant cause of late morbidity and mortality after allogeneic HSCT. cGVHD often manifests as autoimmune syndrome. Thymic epithelial cells (TECs) play a critical role in supporting negative selection and regulatory T‐cell (Treg) generation. Studies have shown that damage in TECs is sufficient to induce cGVHD. We have previously reported that mouse embryonic stem cells (mESCs) can be selectively induced to generate thymic epithelial progenitors (TEPs) in vitro. When transplanted in vivo, mESC‐TEPs further develop into TECs that support T‐cell development. We show here that transplantation of donor‐origin mESC‐TEPs into cGVHD recipients induces immune tolerance to both donor and host antigens and prevents the development of cGVHD. This is associated with more TECs and Tregs. Our results suggest that embryonic stem cell‐derived TEPs may offer a new tool to control cGVHD. Stem Cells Translational Medicine 2017;6:121–130